La responsabilidad civil y penal de los notarios en la realidad ecuatoriana - Uruchima Guapisaca, José Manuel (2026)
This research addresses the civil and criminal liability of notaries in the Ecuadorian context, analyzing the current regulations and their practical application. The exercise of notarial functions in Ecuador is governed by a strong legal framework aimed at ensuring legal certainty through the public trust granted by notaries. However, various problematic areas are identified in implementing and enforcing these officials' responsibilities. Notaries’ civil liability is primarily triggered when negligence or omissions cause harm to the parties involved or third parties in the course of their duties, such as in cases of formal errors or misidentification of grantors. Regarding criminal liability, crimes such as document forgery, bribery, and fraud are among the most common offenses faced by notaries. Despite being clearly defined in the Organic Comprehensive Criminal Code (COIP), the ineffective enforcement of penalties has fostered a perception of impunity. The study highlights that although Ecuadorian regulations are comprehensive, there are deficiencies in their practical application. Penalties imposed in both civil and criminal domains often lack appropriate proportionality, weakening the control system. Furthermore, explicit prohibitions in the Notarial Law, such as the prohibition against drafting simulated deeds or those for direct relatives, are frequently disregarded. This underscores the need to strengthen supervisory and accountability mechanisms in the notarial sphere. The conclusion emphasizes the importance of implementing stricter measures and more effective control mechanisms to ensure the integrity of the notarial system and, consequently, public trust in it. Achieving this requires greater coherence between regulations and their application, as well as more rigorous oversight of notarial functions by the competent authorities.